Productive and economic performance of Arabica coffee and macadamia nut intercropping - Perdoná, Marcos José; Soratto, Rogério Peres; Esperancini, Maura Seiko Tsutsui (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the productive and economic performance of Arabica coffee and macadamia nut intercropping, under rainfed and drip‑irrigation conditions, as well as the financial viability of treatments in three coffee price scenarios. A completely randomized design was used, with six treatments (rainfed sole coffee, irrigated sole coffee, rainfed coffee‑macadamia nut intercropping, irrigated coffee‑macadamia nut intercropping, rainfed sole macadamia nut, and irrigated sole macadamia nut) and ten replicates. The productivity, the area equivalency index, and the economic outcomes of the treatments were evaluated in three coffee price scenarios. Drip irrigation and intercropping increased coffee and macadamia nut yields, in comparison to rainfed monocultures, and generally promoted the same productivity as the coffee irrigated monocultures, as well as higher productivity than the macadamia nut irrigated monocultures. The combined use of intercropping and drip irrigation promotes land‑use efficiency 5‑fold greater than the averages of rainfed monocultures. Irrigated intercropping promotes higher profitability and faster return on investment, making it a viable alternative, especially in periods of lower coffee prices.
Keywords: Coffea arabica; Macadamia integrifolia; intercropping; drip irrigation; coffee selling price; profitability